AN INDUSTRY-INTEGRATED LEARNING MODEL FOR MARITIME VOCATIONAL EDUCATION: DEVELOPMENT AND EVALUATION THROUGH INDUSTRIAL WORKFLOWS AND SIMULATOR-BASED LEARNING - Wegig Pratama; Suhono Suhono; Bambang Sudarsono; Muhammad Amin (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
The gap between Maritime Vocational Education (MVE) and shipping industry demands has resulted in graduates with technical skills but limited workplace readiness. This study developed and evaluated an Industry-Integrated Learning Model (IILM) that integrates industrial workflows, authentic operational scenarios, behavioral assessment, and reflective debriefing into simulator-based learning. Unlike conventional simulator-based approaches that mainly focus on technical performance, IILM embeds industry practices within the learning process to strengthen work readiness. The study employed a modified ADDIE-based Research and Development (R&D) approach involving 60 Nautical Studies students. Data were collected through expert validation, bridge simulator assessment, and the Work Readiness Assessment Rubric (WRAR). The model achieved high feasibility (M = 4.62/5.00), and the experimental group obtained significantly higher post-test scores (M = 84.67) than the control group (M = 71.33, p < 0.001). The findings demonstrate that IILM improves students’ work readiness, particularly in situational awareness and collaborative communication.